2022
DOI: 10.3389/fonc.2022.927706
|View full text |Cite
|
Sign up to set email alerts
|

A novel cuproptosis-related prognostic lncRNA signature and lncRNA MIR31HG/miR-193a-3p/TNFRSF21 regulatory axis in lung adenocarcinoma

Abstract: Lung adenocarcinoma (LUAD) remains the most common subtype of lung malignancy. Cuproptosis is a newly identified cell death which could regulate tumor cell proliferation and progression. Long non-coding RNAs (lncRNAs) are key molecules and potential biomarkers for diagnosing and treating various diseases. However, the effects of cuproptosis-related lncRNAs on LUAD are still unclear. In our study, 7 cuproptosis-related lncRNAs were selected to establish a prognostic model using univariate Cox regression analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…However, in colorectal cancer ( Xu et al, 2019 ), SATB2-AS1 has the effect of inhibiting tumor cell metastasis. Similar to our result, AC026355.1 was reported to be an immune-related gene with tumor suppressor effects by Li et al ( Li et al, 2020 ) In past studies, AL606489.1 has been reported to be associated with autophagy ( Liu et al, 2021 ), ferroptosis ( Guo et al, 2021 ), cuproptosis ( Mo et al, 2022 ) and pyroptosis ( Li et al, 2018 ; Song et al, 2021 ) processes in LUAD tumor cells. LINC 01843 was first shown to be associated with LUAD progression.…”
Section: Discissionsupporting
confidence: 91%
“…However, in colorectal cancer ( Xu et al, 2019 ), SATB2-AS1 has the effect of inhibiting tumor cell metastasis. Similar to our result, AC026355.1 was reported to be an immune-related gene with tumor suppressor effects by Li et al ( Li et al, 2020 ) In past studies, AL606489.1 has been reported to be associated with autophagy ( Liu et al, 2021 ), ferroptosis ( Guo et al, 2021 ), cuproptosis ( Mo et al, 2022 ) and pyroptosis ( Li et al, 2018 ; Song et al, 2021 ) processes in LUAD tumor cells. LINC 01843 was first shown to be associated with LUAD progression.…”
Section: Discissionsupporting
confidence: 91%
“…Our new discovered CuRLsig (AC138965. 37 . Furthermore, our CuRLsigderived risk model signi cantly outperformed all previous-reported models (Li = 0.637, Jin = 0.629, Zeng = 0.679 and CuRLsig-derived score = 0.718 in TCGA set of 3-year) [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies confirmed that N6-methyadenosine-related lncRNAs predicted AML prognosis and the immune landscape [20][21][22]. Moreover, it is worth mentioning that cuproptosis-related lncRNA signature also showed promising prognosis prediction potential in carcinomas, including hepatocellular carcinoma [23], lung adenocarcinoma [24], colon adenocarcinoma [25], and colorectal cancer [26]. However, whether cuproptosis-related lncRNA signature could be utilized for the prediction of AML prognosis and immune response is largely unknown.…”
Section: Introductionmentioning
confidence: 97%